Nutritional composition of baobab (Adansonia digitata L.) fruit pulp sampled at different geographical locations in Kenya - Stadlmayr, B.; Wanangwe, J.; Waruhiu, C.G.; Jamnadass, Ramni H.; Kehlenbeck, K. (Elsevier, 2020)
Baobab (Adansonia digitata L.) is a multipurpose tree indigenous to the semi-arid and sub-humid zones of sub-Saharan Africa. Despite it’s multiple uses and valuable properties, information on its nutritional and phenotypic characteristics is rare, particularly in Eastern Africa. For the present study 64 baobab trees were sampled at six different locations of inland and coastal Kenya and the nutritional composition of 59 samples of fruit pulp was determined, including water, minerals, vitamin C and total acidity. The pulp of the studied baobab fruits is a valuable source of minerals and vitamins, particularly of vitamin C (mean 175 ± 62 mg/100 g edible portion on fresh weight basis (EP)), potassium (mean 1006 ± 280 mg/100 g (EP)) and calcium (mean 375 ± 93 mg/100 g EP). However, we found high tree-to-tree differences for all analyzed parameters with highest coefficients of variation detected for iron (47%), zinc (41%) and vitamin C (36%). Additionally we observed nutritional variations regarding iron, potassium, total acidity and pH value among the six locations. The results of this study will contribute to select superior baobab mother trees for future domestication programs and nutrition interventions and to promote the cultivation and use of baobab in Kenya.